The effects of climate variability on the timing of ichthyoplankton ingress through Beaufort Inlet, NC, USA - Thaxton, William C (East Carolina University, 2019)
Climate change has shifted the timing of seasons in many ecosystems worldwide. Species are responding to these shifting seasons with shifts of their own, both in space via migrations and in time via phenology. However, species vary in the direction and magnitude of these spatial and temporal shifts. As the effects of climate change become more pronounced, this variation in the response of species may disrupt interspecific interactions in ecological communities. Research into the responses of species to climate change is therefore critical to understanding how ecosystems may function in the future. In this thesis I examined one way in which the fall and winter ichthyoplankton community of Beaufort Inlet, North Carolina has responded to environmental variability over the last 27 years. I related changes in sea surface temperature, the Atlantic Multidecadal Oscillation, the North Atlantic Oscillation, offshore wind phenology, nearshore wind strength, and tidal height to the time at which ten species of larval fish ingressed through Beaufort Inlet. I also examined whether any species had exhibited trends in ingress phenology over the last three decades. Species varied in the magnitude of their responses to all of the environmental variables studied, but most shared a common direction of change. Sea surface temperature and northerly wind strength appear to have the largest impact on ingress phenology, with most species advancing their ingress during warm years and delaying ingress during years of strong northerly winds. As sea surface temperatures warm in the coming decades, the average timing of ingress of some species may advance on the order of weeks to months, assuming temperatures do not exceed a threshold at which species can no longer respond. These shifts in ingress could affect the chances of survival of larvae since environmental conditions in the estuarine and pelagic nursery habitats of fishes also vary seasonally. The extent to which larval survival is affected by their changes in phenology will depend on how climate change shapes conditions in estuarine and coastal habitats.
Keywords: South Atlantic Bight; Onslow Bay; Fishes--Larvae--Climatic factors--North Carolina --Beaufort Inlet; Animal welfare--North Carolina--Beaufort Inlet; Phenology--North Carolina--Beaufort Inlet